ANALISIS KINERJA ALAT CALSINER DITINJAU DARI EFISIENSI THERMAL DI PABRIK BATUARAJA II PT. SEMEN BATURAJA (PERSERO) TBK. - Tiara, Anindita Bunga; Anugrah, Rendotian; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Calciner is a heating aid used in all modern rotary kiln products. The calciner is a preheating device and a place for the reaction to occur preliminary calcination before entering the kiln. Calciner has been operating at the right time long enough, considering its use, it is necessary to analyze the efficiency Calciner tool performance. Calciner tool which is a tool that is used as a place for the process of calcining limestone and burning fuel simultaneously in a cement factory. The addition of calciner to the cement plant aims to reduce the burning zone load in the kiln because the fuel to the calciner reaches 60%, increases the production capacity of the kiln, and makes the operation of the kiln more stable. The calciner uses coal as fuel which is in contact with hot air from the kiln (tertiary air) coming from the grate cooler. In the development of this calciner system, each cement plant has a different design, but has the same goal, namely to increase the degree of calcination and increase production capacity and reduce energy consumption, especially heat energy used in the kiln. The purpose of using the Calciner is to reduce the burning load of the rotary kiln. at PT Semen Baturaja (Persero) Tbk. using a preheater with 5 levels, where the calciner is placed after cyclone IV then the calciner results to cyclone V. The calciner has a total height of 59.75 meters with an inner diameter of 7.6 meters. At the top and bottom are cone-shaped where the top cone is larger in diameter than the bottom cone. This is because the feed is in the form of solids and at the bottom enters the tertiary air in the form of gas at PT Semen Baturaja (Persero) Tbk.